Class Action Lawsuit on Civil Issues in Indonesia as Common Law Adoption - Lestari, Maryana; Adiyatma, Septhian Eka (Universitas Negeri Semarang, 2020)
Regulations in Indonesia country must be fulfilled and adhered to, all the provisions in the form of prohibition, injunction and the sanctions that are in the environment of Indonesian society are legal countries. This research aims to analyze the discourse of class action lawsuit practices in Indonesian with comparing civil law system. The research also intended to illuminate the development civil law system practices in the context of class action practices. The research is doctrinal research with normative legal research. The research compared some legal theories concerning to class actions lawsuit in civil law system. The research highlighted and emphasized that the actions and deeds are led to occur harmonious society without touching the rights of others. In civil law issues include problems between individuals and groups and from group to group and individual to individual, who violated the rights and obligations as a result of an agreement. Expanding the law does not rule out a new legal innovation that can make a person who made a report the other party violated his rights in the absence of a prior agreement to do. The research concluded that the class action suit or action lawsuit is a legal order that is embraced by the common law system, but countries that use civil law systems like Indonesia participate adopt this legal order.